2021
DOI: 10.1007/s10811-021-02527-8
|View full text |Cite
|
Sign up to set email alerts
|

Weakened growth, cell division, and energy metabolism, but enhanced resistance, signaling, and anabolism: responses of Ulva prolifera to copper elucidated by omics

Abstract: Ulva spp. have outstanding survivability in copper-rich environments, but research into the interactions between these algae and copper is required. This study combined transcriptomics, proteomics, and metabolomics to investigate the expression of various metabolites in Ulva prolifera after exposure to 10 mg L −1 of copper sulfate for 12 h. The results showed that copper stress in U. prolifera mainly manifested as a reduction in transcription and translation, which was related to gene expression, protein activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…However, the results of this study revealed Due to the controlled and closed system used in this study, the factors interfering with the absorption of Zn by Ulva lactuca L. must come from the initial Zn content and Ulva lactuca L. itself. Although Zn is an essential element for the biological metabolism of algae, when a specific concentration is exceeded, Zn can also become a substance harmful to organisms [17]. In order to obtain more accurate measurements, the initial Zn concentration used in the experiment far exceeded the Zn concentration level in normal seawater.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%
“…However, the results of this study revealed Due to the controlled and closed system used in this study, the factors interfering with the absorption of Zn by Ulva lactuca L. must come from the initial Zn content and Ulva lactuca L. itself. Although Zn is an essential element for the biological metabolism of algae, when a specific concentration is exceeded, Zn can also become a substance harmful to organisms [17]. In order to obtain more accurate measurements, the initial Zn concentration used in the experiment far exceeded the Zn concentration level in normal seawater.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%
“…Studies have also explored the underlying mechanisms of action of these stress responsive genes in seaweeds. Some of the seaweeds that have been studied at the molecular level include Ulvaceae such as U. prolifera [ 18 , 19 ], U. linza [ 20 ], and U. compressa [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, U. prolifera is a macroalga characterized by high palatability and high levels of microelements, making it an important food item for marine herbivores and a candidate additive for animal feeds [37]. It has been widely used as an algal model to detect physiological changes due to various stresses by means of metabolomic investigations [38,39].…”
Section: Introductionmentioning
confidence: 99%